Prospects of earthworm coelomic fluid as a potential therapeutic agent to treat cancer - Haque S.; Hussain A.; Almalki A.H.; Aldawsari M.F.; Lal B.; Rai A.K.; Srivastava M.; Fiołka M. (My University, 2025)
Cancer is a major public health concern because it is one of the main causes of morbidity and mortality worldwide. As a result, numerous studies have reported the development of new therapeutic compounds with the aim of selectively treating cancer while having little negative influence on healthy cells. In this context, earthworm coelomic fluid has been acknowledged as a rich source of several bioactive substances that may exhibit promising anticancer activity. Therefore, the objective of the present review is to evaluate the findings of the reported studies exploring the antitumor effects of coelomic fluid in the context of its possible utilization as a natural therapeutic agent to cure different types of cancer. The possible mechanisms underlying the coelomic fluid’s anticancerous potential as well as the possibility for future development of cutting-edge therapeutic agents utilizing coelomic fluid-derived natural bioactive compounds to treat cancer disorders have been discussed along with future challenges. In addition, the feasibility of encapsulation of bioactive compounds derived from coelomic fluid with nanomaterials that could be further explored to attain more effective anticancer competence is discussed. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.